2022
DOI: 10.1002/1348-9585.12322
|View full text |Cite
|
Sign up to set email alerts
|

Working hours, on-call shifts, and risk of occupational injuries among hospital physicians: A case-crossover study

Abstract: Objective To investigate the association of hospital physicians’ working hours and on‐call shifts with the risk of occupational injuries. Methods In this nested cohort study of 556 Finnish hospital physicians, we linked electronic records from working‐hour and on‐call duty payroll data to occupational injury data obtained from the Finnish Workers’ Compensation Center for the period 2005–2019. We used a case‐crossover design with matched intervals for a 7‐day ‘case windo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Os trabalhadores do setor da saúde representam 10% da mão-de-obra total da União Europeia (EU), sendo significativa a proporção destes que trabalham em hospitais (3). O trabalho em meio hospitalar é suscetível de causar danos para a saúde tanto pela ocorrência de acidentes e doenças profissionais devido à exposição aos riscos inerentes às tarefas, como pela exposição frequente a situações de stress e de fadiga física e mental (4) (5). Segundo a Administração Central dos Serviços de Saúde (ACSS), em 2013, por cada 1000 trabalhadores do Serviço Nacional de Saúde (SNS), 53 foram vítimas de AT, 75% correspondendo a assistentes operacionais e enfermeiros (3).…”
Section: Discussionunclassified
“…Os trabalhadores do setor da saúde representam 10% da mão-de-obra total da União Europeia (EU), sendo significativa a proporção destes que trabalham em hospitais (3). O trabalho em meio hospitalar é suscetível de causar danos para a saúde tanto pela ocorrência de acidentes e doenças profissionais devido à exposição aos riscos inerentes às tarefas, como pela exposição frequente a situações de stress e de fadiga física e mental (4) (5). Segundo a Administração Central dos Serviços de Saúde (ACSS), em 2013, por cada 1000 trabalhadores do Serviço Nacional de Saúde (SNS), 53 foram vítimas de AT, 75% correspondendo a assistentes operacionais e enfermeiros (3).…”
Section: Discussionunclassified
“…The effect of long periods of consecutive working days has been studied in the medical and occupational health literatures, following Estryn-Behar et al (1990) who introduced it as an index of "strain caused by schedule". This literature provides evidence that a high level of consecutive working days is associated with fatigue and sleepiness (Boivin and Boudreau 2014), decreased process speed (Gershengorn et al 2020) and cognitive functioning (Proctor et al 1996), occupational injuries (Garde et al 2020, Ropponen et al 2022, increased feelings of depression and confusion (Proctor et al 1996), headache, migraine, or pain (Matre et al 2022), and physical and emotional exhaustion (Gaines and Jermier 1983, Welp et al 2016, Liu et al 2020, Sagherian et al 2020, González-Gil et al 2021. By connecting this literature with the healthcare operations literature on staffing levels and daily workload management, we contribute to our understanding of the interplay between the level of team-averaged consecutive working days (ACDW) and daily team workload, measured by nurse-to-patient ratios (NPR) on the day.…”
Section: Contribution To the Literaturementioning
confidence: 99%
“…The number of consecutive working days has been used in the literature as an index of "stress caused by the schedule" (Estryn-Behar et al 1990) and this literature supports the hypothesis that an increase in the number of consecutive working days reduces service qualilty. As mentioned in Section 2, an increase of consecutive working days has been associated with depression and confusion (Proctor et al 1996), occupational injuries (Ropponen et al 2022), headache and pain (Matre et al 2022), impaired cognitive effectiveness (James et al 2021) and chronic fatigue and sleepiness (Boivin andBoudreau 2014, Elfering et al 2021), which has been demonstrated to affect worker performance negatively (Veasey et al 2002, Tsafrir et al 2015, Schwartz et al 2021.…”
Section: Baseline Effect Of the Number Of Consecutive Working Daysmentioning
confidence: 99%
“…The design is most appropriately employed when exposure is intermittent, the effect on risk is immediate and transient, and the outcome is abrupt. Thus, for example, casecrossover designs have been used to study the impact of shift schedule characteristics (eg, shift length, time of day, on-call shifts, shift intensity and weekly work hours) on outcomes such as occupational injuries and on short term sickness absence (9)(10)(11)(12)(13)(14). However, the approach has the potential to be applied more widely, eg, to study single changes in exposure level, gradual effects on risk and outcomes with insidious onsets (15).…”
Section: Scientific Challenges Of Studying Shift Schedule Designmentioning
confidence: 99%